Clinical-epidemiological characterization of leprosy cases with physical disabilities - Gleciane Costa de Sousa; Francilene de Sousa Vieira; Déborah Éllen Pinheiro Oliveira; Ederson dos Santos Costa; Maria Edileuza Soares Moura (Universidade Federal do Ceará, 2017)
To characterize the clinical-epidemiological profile of cases of multibacillary leprosy, diagnosed with physical disabilities. Methods: this is a cross-sectional and retrospective study. The sample consisted of 276 cases of diagnosed leprosy. Results: leprosy mainly affects males, of brown skin color, low education and with a mean age of 51.96 years old (standard deviation, SD=20.33 years old). The Virchowian and dimorphic clinical forms are mainly responsible for the transmission of the disease and the development of physical disabilities. Decreased or lost sensation in hands and feet, trophic ulcers and traumatic injuries, as well as clawed hands were the physical disabilities prevalent in the study. Conclusion: the cases with physical disabilities are predominantly affected by multibacillary clinical forms, and they can be inferred in the maintenance of the transmission chain and the late detection of severe forms of leprosy.